Problem and Challenges Faced by Students, Parents, and Teachers in Google Classes & Television Lessons - Tshewang Dorji (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The qualitative study was carried out under Thimphu Thromde, Bhutan, to assess the use of Google class and Television lessons during the emergence of COVID-19 in the 2020 academic year. The study used Google class & Television lesson observations to gain the first-hand experience and face-to-face interviews with students, parents, and teachers to get in-depth views. The Google class and television lesson observation and interview data were analyzed using emerging themes. The findings revealed that Google class and Television lessons played an essential role in making up lessons lost during schools' closure. However, the study further revealed some pertinent issues related to the Google class and Television lessons, including students resorting to copying assignments and homework directly from friends or copying directly from textbooks and the internet. Students were overburden by the heavy load of assignments assigned by different subject teachers, among many others. More preparedness and training for teachers in ICT based pedagogy was required. The study might draw policy attention to consider the problem and challenges before implementing Google class and Television lessons shortly to avoid pitfalls. The study was limited to the Thimphu Thromde, Bhutan, using a small sample size of students, parents, and teachers. A future mixed-method research approach uses surveys with students, parents, and teachers; focus group discussions with students, parents, and teachers; and policymakers' interviews are recommended.